Modelling of Microalgae Growth and Oil Production by Using Sewage and Carbon Dioxide for Biodiesel - Ding, Gong Tao; Jailani, Salihon (2009)
With the depletion of the world fossil oil reserves, microalgae biodiesel might become one of the economic, renewable and carbon-neutral sources of transportation biofuels. This study investigates marine microalgae growth and biodiesel production by cultivating highly productive oleaginous microalgae at large scale using sewage as nutrient supply and waster CO2 as carbon source. Five strains of marine microalgae will be screened in the laboratory for their biomass productivity and lipid content. The best strain will be optimised for the cultivation parameter, including initial pH value, dissolved carbon dioxide concentration, proportion of sewage mixture and illumination intensity. The result showed Chlorella and Nannochloropsis Local have the better biomass production.